iFlexIELTS: an AI-driven IELTS test prep centre in Vietnam - Lai, Ngan Tam (2025)
This report presents a complete business plan for iFlexIELTS, a unique mix of cost-effectiveness, technology-enhanced efficiency, human capabilities, and tailoring based on learning styles. This enables iFlexIELTS to provide the most effective IELTS preparation outcomes conveniently online.